Improving student’s mathematical critical thinking skills through K-N-W-S strategy - R Amalia; E Cahya; B A Priatna (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The research aims to analyze the improvement of mathematical critical thinking skills of student through KNWS Strategy. Quasi experiment was used as research method with pretest-posttest control group design. It was conducted at one of the middle schools in Bandung. Population in this reasearch was 8th grade student of ten parallel classes. Two classes ware taken randomly as the reseach sample which consisting of 35 students in the experimental group and 33 students in the control group. The result showed that the improvement of mathematical critical thinking skills of students who acquired K-N-W-S strategy learning was higher significantly than students who acquired conventional strategy.